Magnetic nanometer COF material and application thereof in determination of PAEs plasticizer in water body

By fe3O4@TAPOB-COF, a magnetic covalent organic frame material wrapped in the surface of magnetic iron oxide nanoparticles, the problem of poor stability of magnetic nanomaterials in environmental water bodies is solved, and efficient enrichment and determination of PAEs plasticizers is achieved, which significantly improves sensitivity and reuse times.

CN119565575APending Publication Date: 2025-03-07豫章师范学院
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411776070.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing magnetic nanomaterials have poor stability when used in environmental water bodies, resulting in a decrease in adsorption performance and the inability to effectively measure PAEs plasticizers in water bodies.

Method used

The magnetic covalent organic frame material Fe3O4@TAPOB-COF is adopted to enhance the stability and selectivity of the material, and the enrichment pretreatment of PAEs in ambient water bodies is achieved.

Benefits of technology

The stability and selectivity of the material are significantly improved, and efficient enrichment and determination of 6 common PAEs are achieved, with a sensitivity of 2 to 8182 times. The material can be reused more than 6 times, and it is resistant to high temperatures above 300℃ and weak acid and weak alkali solution environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119565575A_ABST
    Figure CN119565575A_ABST
Patent Text Reader

Abstract

The invention relates to the field of analytical chemistry, in particular to a magnetic nanometer COF material and application of the magnetic nanometer COF material to determination of PAEs plasticizers in water. The preparation method comprises the following steps: adding tetraethoxysilane into Fe3O4 magnetic nanoparticles to obtain Fe3O4 (at) SiO2 with a core-shell structure, carrying out amination to form NH2-Fe3O4 (at) SiO2, then adding DHA (docosahexaenoic acid), carrying out condensation to obtain Fe3O4 (at) SiO2 (at) DHA, and finally adding TAPOB to obtain Fe3O4 (at) TAPOB-COF. According to the method disclosed by the invention, a new pretreatment method is established on the basis of the self-made Fe3O4-coated TAPOB-COF, and efficient detection of six common PAEs in an environmental water body is realized. Through pretreatment after experimental optimization, the sensitivity is improved by 2-8182 times compared with that of a common method reported in literatures. The maximum adsorption capacities of the six substances, namely DMP, DEP, BBP, DBP, DEHP and DNOP, are 312 mu g / g, 500 mu g / g, 714 mu g / g, 128 mu g / g, 111 mu g / g and 620 mu g / g respectively. The material can be repeatedly used for more than 6 times, and can resist high temperature of more than 300 DEG C and weak acid and weak base solution environments, so that the material has a wide application prospect in the aspect of analysis and detection technology of environmental water containing PAEs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of analytical chemistry, and in particular to a magnetic nano-COF material and an application thereof in determining a PAEs plasticizer in water. Background Art

[0002] Phthalate esters (PAEs) are also called phthalates. In recent years, PAEs have been widely used in the production of toys, cosmetics, food packaging and textiles due to their high transparency, strong plasticity and low price. However, PAEs are environmental hormone substances with strong carcinogenic, teratogenic and mutagenic properties. They can easily migrate out of the matrix and accumulate in the environment, which can have adverse effects on humans and animals through drinking water, breathing, skin contact and other pathways. Among them, dioctyl phthalate (DNOP), dimethyl phthalate (DMP), di(2-ethylhexyl) phthalate (DEHP), butyl benzyl phthalate (BBP), diethyl phthalate (DEP) and dibutyl phthalate (DBP) are the six most common PAEs plasticizers, so they are listed as priority pollutants harmful to humans and the environment by the European Union.

[0003] In the pretreatment technology of PAEs in water, solid phase microextraction, liquid phase microextraction, dispersed liquid-liquid microextraction, stir bar adsorption extraction and other pretreatment technologies have developed rapidly in recent years, but most of them have the disadvantages of complex operation, large amount of extraction solvent, poor selectivity, easy secondary pollution to the environment and poor recovery rate. In contrast, magnetic nanomaterials not only have the advantages of superparamagnetism and large specific surface area, but also have the advantages of simple preparation method, reusability and environmental friendliness. Therefore, the application of magnetic nanomaterials to magnetic solid-phase extraction (MSPE) can make it simple, time-saving, labor-saving and high extraction efficiency. In addition, iron ore is relatively abundant in nature. Using it as a magnetic adsorption material can also greatly reduce the cost of sample pretreatment technology. However, due to the high surface activity of magnetic nanomaterials, if they are directly used in environmental water, they are prone to agglomeration, thereby reducing their stability, resulting in a sharp decrease in their surface area and a decrease in adsorption performance. Summary of the invention

[0004] Based on the poor stability of magnetic nanomaterials, there is currently no effective determination of PAEs plasticizers in environmental water using magnetic nanomaterials. This paper proposes a magnetic covalent organic framework material (Fe 3 O 4@TAPOB-COF), which enhances the stability and selectivity of the material, and realizes the enrichment pretreatment of 6 common PAEs in environmental water bodies in a simple and efficient manner. Finally, PAEs can be effectively determined using conventional analytical methods.

[0005] The "covalent organic framework" (COF) described in the present invention is a new type of multifunctional crystalline organic polymer composed entirely of light elements (C, H, O, N, B, etc.) and constructed by organic monomers through covalent bonds. COF materials have the advantages of low density, large specific surface area, adjustable pore size, strong functionality, etc., and have predictable design at the atomic level, including geometric, structural and functional properties. COF is synthesized on the basis of dynamic covalent chemistry, and can perform "error checking" and "proofreading" on the reaction system, which is a key process for the formation of crystals and ordered structures. COF materials can achieve the adsorption of different pollutants, including organic pollutants and inorganic heavy metal pollutants in different media, by modifying different functional groups. These excellent properties enable COF to exhibit the advantages of large adsorption capacity, fast adsorption rate, strong stability and good repeatability when adsorbing pollutants.

[0006] The specific plan is as follows:

[0007] A magnetic nano COF material having a core and a COF outer layer, wherein the core contains Fe 3 O 4 @SiO 2 , the outer layer of the COF contains TAPOB (1,3,5-(4-aminophenoxy)benzene).

[0008] Furthermore, the inner core also contains DHA (2,5-dihydroxyterephthalaldehyde), and the inner core and the outer layer of COF are connected by DHA.

[0009] Furthermore, the Fe 3 O 4 @SiO 2 The DHA is connected by condensation of amino group and aldehyde group.

[0010] The present invention uses COF material to wrap magnetic iron oxide nanoparticles (Fe 3 O 4 The surface of COF materials can be made into composite materials, which can increase the specific surface area, reduce agglomeration, and increase the adsorption stability and efficiency. On the other hand, COF materials bonded with functional groups such as benzene rings can increase the selectivity and application range of PAEs plasticizers.

[0011] Furthermore, the Fe 3 O 4The particle size of the material is 201-243 nm, and the particle size of the magnetic nano COF material is 295-306 nm.

[0012] In the present invention, "Fe 3 O 4 "Magnetic iron oxide nanoparticles" "Fe 3 O 4 “NPs” refers to unmodified or unmodified FeO nanoparticles.

[0013] In some embodiments, the amino group can be composed of SiO 2 and 3-aminopropyltriethoxysilane (APTES) to generate Fe 3 O 4 @SiO 2 After reacting with APTES, the Fe 3 O 4 @SiO 2 The surface is modified with amino groups, and the DHA has aldehyde groups. The amino groups condense with the aldehyde groups of DHA to cover the DHA on the Fe 3 O 4 @SiO 2 surface, strengthening the structure of the core, i.e., Fe 3 O 4 @SiO 2 @DHA.

[0014] And Fe 3 O 4 @SiO 2 @The aldehyde groups in DHA and the amino groups in TAPOB form an imine bond condensation, and the free aldehyde groups in DHA react with the amino groups in TAPOB to form a continuous and uniform COF outer layer.

[0015] On the other hand, the present invention discloses a pretreatment reagent, wherein the pretreatment reagent contains the magnetic nano-COF material.

[0016] Furthermore, the pretreatment reagent also contains a desorption reagent, and the desorption reagent is selected from acetonitrile, ethanol, methanol or isopropanol.

[0017] Furthermore, the volume of the desorption reagent is 2-4 mL.

[0018] On the other hand, the present invention also discloses a method for preparing the magnetic nano-COF material, comprising the following steps:

[0019] (1) Synthesis of Fe 3 O 4 @SiO 2 Magnetic microspheres;

[0020] (2) Amination of the Fe 3 O 4 @SiO 2 Magnetic microspheres are NH 2 -Fe 3 O 4 @SiO 2 ;

[0021] (3) DHA and NH 2 -Fe 3 O 4 @SiO 2 The reaction generates Fe 3 O 4 @SiO 2 @DHA;

[0022] (4) the Fe 3 O 4 @SiO 2 @DHA reacts with TAPOB to generate the magnetic nano-COF material, namely Fe 3 O 4 @TAPOB-COF.

[0023] Furthermore, the TAPOB and Fe 3 O 4 @SiO 2 @DHA ratio is 1 / 2~2.

[0024] On the other hand, the present invention discloses the use of the magnetic nano-COF material and the pretreatment reagent for determining PAEs plasticizers; preferably, the use is to determine PAEs plasticizers in environmental water.

[0025] Further, the PAEs plasticizer is selected from dioctyl phthalate (DNOP), dimethyl phthalate (DMP), di(2-ethylhexyl) phthalate (DEHP), butyl benzyl phthalate (BBP), diethyl phthalate (DEP) and dibutyl phthalate (DBP).

[0026] On the other hand, the present invention discloses a pretreatment method for determining PAEs plasticizers in environmental water, characterized in that it comprises the following steps:

[0027] (1) mixing the magnetic nano-COF material of claim 1 or 2 with environmental water;

[0028] (2) Ultrasonic magnetic attraction to separate unabsorbed impurities;

[0029] (3) Ultrasonic desorption.

[0030] Preferably, the method may further include the step of: (4) filtering the magnetic nano-COF material treated in step (3).

[0031] Furthermore, the filtration may be performed using a 0.22 μm nylon 66 organic filter membrane.

[0032] Filtration can further remove impurities, making the composition of magnetic nano-COF material and PAEs plasticizer more uniform, which is convenient for subsequent determination.

[0033] Furthermore, the ultrasonic magnetic adsorption time is more than 20 minutes, the ultrasonic desorption time is more than 10 minutes, and the desorption reagent used in the ultrasonic desorption is selected from acetonitrile, ethanol, methanol or isopropanol.

[0034] Furthermore, the ultrasonic magnetic attraction time is more than 40 minutes.

[0035] Among them, 20 min can meet the adsorption conditions required for the determination, and 40 min can make the adsorption more complete.

[0036] The magnetic attraction can directly use a magnet to adsorb the magnetic nano-COF material.

[0037] On the other hand, the present invention also discloses a method for determining PAEs plasticizers in environmental water, comprising the pretreatment method and the detection method, wherein the detection method is selected from gas chromatography, liquid chromatography, gas chromatograph-mass spectrometry, liquid-mass spectrometry, micellar electrokinetic capillary chromatography or Fourier transform infrared spectroscopy, and preferably, the detection method is liquid-mass spectrometry.

[0038] Furthermore, the LC-MS method parameters are as follows:

[0039] Chromatographic column: Agilent EclipsePlus C18 column (50mm×2.1mm, 1.8μm). Mobile phase: phase A (0.2% formic acid in water) and phase B (methanol). The initial flow rate was 0.4mL / min at 35℃ column temperature by gradient elution program, and the injection volume was 5μL. Gradient elution program: 0~5min, 50%→50%B; 5~12min, 50%B→95%B; 12~18min, 95%→50%B; 18min, STOP.

[0040] The MS signals of the analytes and internal standards (IS) were detected by the multiple reaction monitoring (MRM) mode of the mass spectrometer, and the electrospray ionization (ESI) was in the positive ion mode. The 100 μg / L standard solution and 1.0 mg / L IS solution were directly introduced to optimize the ion source and other MS / MS parameters. Pure nitrogen (>99%) was used as the nebulizer gas and drying gas, and high-purity nitrogen (>99.999%) was used as the collision gas. The gas flow rate was 13 L / min, and the sheath gas flow rate was 11 L / min. The ion source temperature was controlled at 300°C, and the sheath gas temperature was controlled at 250°C. The capillary voltage was 4000 V, and the nozzle voltage was 1500 V. The pressure of nitrogen in the nebulizer was 35 psig.

[0041] Beneficial effects:

[0042] The present invention synthesizes a novel magnetic nano-COF material with a typical core-shell structure at room temperature. The synthesis method is simple and rapid. Magnetic extraction is utilized, and the entire pre-treatment method is also simple and convenient.

[0043] The magnetic nano-COF material of the present invention is used in the pretreatment process, and after the conditions are optimized, the sensitivity is improved by 2 to 8182 times compared with the common methods reported in the literature. The magnetic nano-COF material of the present invention is used for the first time to propose the maximum adsorption amounts of six substances, DMP, DEP, BBP, DBP, DEHP, and DNOP, which are 312, 500, 714, 128, 1111, and 620 μg / g, respectively, and the material can be reused more than 6 times, and can withstand the use of high temperatures above 300°C and weak acid and weak alkali solution environments, thus expanding the scope of application and having important significance for the determination of PAEs in various environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 :Preparation of Fe3O4@TAPOB-COF and the principle diagram of PAES determination in environmental water;

[0045] Figure 2 : Infrared spectra of Fe3O4 NPs, Fe3O4@SiO2 and Fe3O4 NPs@TAPOB-COF;

[0046] Figure 3 :XPS measurement spectrum of Fe3O4 NPs@TAPOB-COF;

[0047] Figure 4 :Measure the binding energy spectra of oxygen (O1s), nitrogen (N1s), carbon (C1s), and silicon (Si2p);

[0048] Figure 5 : Measure the peak fitting diagram of carbon (C1s) binding energy spectrum;

[0049] Figure 6 :Fe 3 O 4 NPs, Fe 3 O 4 @SiO 2 , Fe 3 O 4 @TAPOB-COF hysteresis loop diagram of three magnetic materials;

[0050] Figure 7 :Fe 3 O 4 NPs, Fe 3 O 4 @SiO 2 , Fe 3 O 4 @XRD pattern of TAPOB-COF microspheres;

[0051] Figure 8 :Fe 3 O 4 NPs and Fe 3 O 4 @TAPOB-COF scanning electron microscope and transmission electron microscope images; a.×40Kmagnification of Fe 3 O 4 NPs; b.×300K magnification of Fe 3 O 4 NPs; c.×100Kmagnification of Fe 3 O 4 @TAPOB-COF;d.×200K magnification of Fe 3 O 4 @TAPOB-COF;e.and f.are the TEM images of Fe 3 O 4 @TAPOB-COF;

[0052] Fig. 9 :Six plasticizers and corresponding internal standard chromatograms (external standard c = 100μg / L, internal standard c = 10μg / L)

[0053] a.DMP b.DMP-d 4 c.DEP d.DEP-d 4 e.BBP f.BBP-d 4

[0054] g.DBP h.DBP-d 4i.DEHP j.DEHP-d 4 k.DNOP l.DNOP-d 4 DETAILED DESCRIPTION

[0055] Many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar modifications without violating the connotation of the present invention, so the present invention is not limited to the specific implementation disclosed below.

[0056] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0057] Example 1Fe 3 O 4 Preparation of @TAPOB-COF magnetic covalent organic framework materials

[0058] Preparation process Figure 1 As shown,

[0059] The details are as follows:

[0060] (1)Fe 3 O 4 @SiO 2 Synthesis of magnetic microspheres

[0061] Weigh 50-250 mg Fe 3 O 4 NPs were placed in a 100mL three-necked bottle, and 8-40mL of anhydrous ethanol and 4mL of water were added in sequence, and ultrasonic dispersion was performed for 30min. Under magnetic stirring, 1-5mL of concentrated ammonia water and 0.4-2mL of tetraethyl orthosilicate were added dropwise in sequence, and stirring was continued for 14h at room temperature. Subsequently, the black product was separated from the solution under an external magnetic field. The solid product was washed three times with 150mL of ethanol to remove unreacted tetraethyl orthosilicate, and then washed three times with ultrapure water to make the solution neutral. The obtained Fe 3 O 4 @SiO 2 Dry under vacuum at 80°C for 10 h and set aside.

[0062] (2) Amino-functionalized magnetic microspheres (NH 2 -Fe 3 O 4 @SiO 2 )

[0063] Prepare 50-250 mg Fe 3 O 4 @SiO 2 Disperse in 20-120 mL of isopropanol and add 0.1-0.5 mL of silane coupling agent (3-aminopropyltriethoxysilane, APTES) under continuous stirring. After stirring for 9 hours, NH 2 -Fe 3 O 4 @SiO 2 The obtained microspheres were washed with deionized water and ethanol and dried at 60 °C for several hours.

[0064] (3) DHA functionalized magnetic microspheres (Fe 3 O 4 @SiO 2 @DHA) Synthesis

[0065] In this step, a template-modified polymerization reaction was performed to coat the surface of MNPs with 2,5-dihydroxyterephthalaldehyde (DHA): NH 2 -Fe 3 O 4 @SiO 2 (15-150 mg) and DHA (2.2-220 mg) were dispersed in 1-10 mL of dioxane solution, and 15-150 μL of glacial acetic acid (HAc) was slowly added to the reaction system. After stirring for 3 min, the mixture was sealed in a stainless steel autoclave lined with polytetrafluoroethylene and heated at 120 ° C for 1 hour to allow NH 2 -Fe 3 O 4 @SiO 2 The amino groups in the DHA react with the aldehyde groups in the DHA. 3 O 4 @SiO 2 @DHA and washed with dioxane, DMF and mesitylene. The modified product was dried at 50 °C overnight for the next experiment.

[0066] (4) Magnetic covalent organic framework materials (Fe 3 O 4 Synthesis of @TAPOB-COF

[0067] Fe 3 O 4 @SiO 2@DHA (1-100 mg), 1,3,5-(4-aminophenoxy)benzene (TAPOB, 0.56-56 mg,) and DHA (0.44-44 mg) were uniformly dispersed in acetonitrile and sonicated for 1 min. Glacial acetic acid was then added dropwise to the reaction system and sonicated until completely mixed. After standing for 72 hours at room temperature, the resulting precipitate was collected using an external magnetic force. The first stage involves Fe 3 O 4 @SiO 2 @The aldehyde groups in DHA and the amino groups in TAPOB form an imine bond condensation. The free aldehyde groups in DHA react with the amino groups in TAPOB to form a continuous and uniform COF layer. The precipitate is then washed several times with tetrahydrofuran and anhydrous ethanol and dried in vacuum at room temperature.

[0068] Example 2Fe 3 O 4 Characterization of @TAPOB-COF magnetic covalent organic framework materials

[0069] The structure, magnetism and surface conditions of the above-mentioned magnetic nanomaterials, modified magnetic nanospheres and magnetic covalent organic framework materials were characterized by infrared spectrometer, X-ray photoelectron spectrometer, X-ray diffractometer, vibrating sample magnetometer, scanning electron microscope and transmission electron microscope.

[0070] (1) Infrared spectroscopy (IR) characterization

[0071] Characterization method: Take a small amount of Fe 3 O 4 NPs, Fe 3 O 4 @SiO 2 with Fe 3 O 4 NPs@TAPOB-COF was added with KI solid and pressed into tablets for testing.

[0072] The results are as follows Figure 2 As shown, we can see the characteristic peak of Si-O-Si (1100cm -1 about) and Si-OH characteristic peak (949cm -1 ) in Fe 3 O 4 @SiO 2 with Fe 3 O 4 @TAPOB-COF has strong absorption, while Fe 3 O 4 NPs have no corresponding absorption peaks. The three materials have a peak at 470 cm -1 With 550cm -1There are Fe-O-Fe absorption peaks at 1606cm -1 There is a strong absorption peak at 1300cm -1 The CN peak on the benzene ring appeared, indicating that the condensation reaction of Schieff base occurred, and the peak at 1153 cm -1 With 1201cm -1 It may be the COC absorption peak of aromatic ether after TAPOB reaction. However, the peaks at 1493 and 1452 cm -1 The C=C absorption peaks of the benzene ring may be at 803 and 830 cm -1 The absorption peak of CH of m-triphenylene may be at 3400cm -1 The peak at is a water absorption peak, which may be due to the fact that the sample is not absolutely dry. This fully shows that the composite material Fe 3 O 4 @TAPOB-COF was successfully synthesized.

[0073] (2) X-ray Photoelectron Spectroscopy (XPS) Test

[0074] Test method: Take an appropriate amount of sample and press it onto the sample plate. Place the sample into the sample chamber of the Thermo Scientific K-Alpha XPS instrument. The pressure in the sample chamber is less than 2.0×10 -7 mbar, the sample was sent into the analysis chamber, the spot size was 400 μm, the operating voltage was 12 kV, and the filament current was 6 mA; the full spectrum scanning energy was 150 eV, and the step size was 1 eV; the narrow spectrum scanning energy was 50 eV, and the step size was 0.1 eV.

[0075] The results are as follows Figure 3-5 As shown, Figure 3 The Fe 3 O 4 @The chemical composition of TAPOB-COF materials, such as Figure 4 As shown, the wide scan XPS spectrum shows that the binding energies attributed to oxygen (O1s), nitrogen (N1s), carbon (C1s), and silicon (Si2p) are approximately 532.67, 398.66, 284.49, and 103.39 eV.

[0076] The original C1S XPs spectrum data was imported using Avantage software provided by Thermo Scientific for peak fitting. Figure 5The fine scanning spectrum of C1 showed that the binding energies of 284.36, 285.01, 285.60, and 286.18 eV were assigned to C=C, C=N, CN, and CO, respectively (Lu et al., 2020), and these results also confirmed the wrapping of the COF shell.

[0077] Table 1 gives the Fe 3 O 4 X-ray photoelectron spectroscopy (XPS) results of @TAPOB-COF. The simultaneous presence of C, Si, O, and N elements on the surface of magnetic microspheres indicates that Fe 3 O 4 Successful synthesis of TAPOB-COF microspheres.

[0078] Table 1Fe 3 O 4 @The corresponding contents of the four elements in TAPOB-COF composite materials

[0079]

[0080] (3) Hysteresis loop (VSM) test

[0081] Test method: Weigh an appropriate amount of magnetic sample for testing, install the sample on the VSM device, adjust the saddle point, write the test program according to the test requirements, and then start the test; after the test is completed, copy the data and use Origin for graphing.

[0082] The results are as follows Figure 6 As shown, in order to study the magnetic properties, Fe 3 O 4 NPs, Fe 3 O 4 @SiO 2 , Fe 3 O 4 @TAPOB-COF magnetic material hysteresis curve. Fe 3 O 4 NPs, Fe 3 O 4 @SiO 2 , Fe 3 O 4 @TAPOB-COF all exhibit superparamagnetic properties, with magnetic saturation values ​​of 57.2emu / g, 27.0emu / g, and 12.7emu / g, respectively, indicating that the materials can be separated from the solution by an external magnetic field. 3 O 4 Compared with NPs, the magnetization intensity of the latter two adsorbents was significantly reduced, which may be related to the non-magnetic SiO 2This is related to the encapsulation of COFs. However, this magnetization intensity is sufficient to achieve polymerization through an external magnetic field in a relatively short time and can be effectively separated from the solution.

[0083] (4) X-ray diffraction (XRD) characterization

[0084] Characterization method: The material sample is ground evenly and placed in an empty slot, evenly dispersed, flattened with a glass slide and placed in an X-ray powder diffractometer. The test conditions of the fully automatic multifunctional diffractometer are: Cu Kα ray source, working current 0.3mA, generator power 9kW, scanning range wide angle 5-130°, acquisition time 600s, scanning rate 10° / min. The test was performed using a SolstiX workstation.

[0085] X-ray diffractometer (XRD) is a detection method used to determine the structure and composition of a substance. 3 O 4 NPs, Fe 3 O 4 @SiO 2 , Fe 3 O 4 @TAPOB-COF crystal structure and phase purity. Figure 7 As shown, Fe 3 O 4 NPs, Fe 3 O 4 @SiO 2 , Fe 3 O 4 The XRD spectrum of @TAPOB-COF shows that the diffraction peak positions at 35.5°, 43.5°, 53.5° and 62.5° are basically consistent, confirming that the product has a good crystal structure. However, the peak intensity of the latter is weakened, which may be due to the SiO 2 The crystallinity of Fe layer and COF layer is low. 3 O 4 The weak peak of @TAPOB-COF at 25.81° is attributed to COF.

[0086] (5) Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) characterization

[0087] a. Scanning electron microscope characterization method: The sample is directly glued on the conductive glue to prepare the sample, and the gold spraying method is used for testing. The acceleration voltage is 15KV and the working distance is about 6mm.

[0088] b. Transmission electron microscopy characterization method: Take a small amount of powder sample and disperse it in ethanol, ultrasonically disperse it for 10 minutes, drop an appropriate amount of dispersion on the grid, dry it, and then inject it. The acceleration voltage is 200KV.

[0089] The results are as follows Figure 8 As shown, ad is Fe 3 O 4 NPs and Fe 3 O 4 @TAPOB-COF scanning electron microscope (SEM) image, Figure ef is Fe 3 O 4 @Transmission electron microscopy (TEM) image of TAPOB-COF.

[0090] In Figure a, Fe 3 O 4 The overall shape of NPs is a relatively regular sphere, and its particle size is between 201 and 243 nm, which can meet the particle size requirements of nanomaterials. After being magnified 300K times, it can be seen from Figure b that there are many particles and channels on the surface of the microspheres.

[0091] After multiple steps of modification, Fe 3 O 4 The particle size of @TAPOB-COF microspheres is between 295 and 306 nm. After being wrapped layer by layer, the particle size increases, which is in line with the experimental expectations. After being magnified 200K times, it can be seen from Figure d that the surface of the microspheres is relatively thicker than that of Fe 3 O 4 The loose pores of NPs were significantly reduced, indicating that Fe 3 O 4 The surface of NPs may be covered with a denser COF layer, which will be further confirmed by transmission electron microscopy (TEM).

[0092] Figures e and f show that Fe 3 O 4 @TAPOB-COF nanomaterials exhibit a typical wrapping structure, in which the covalent organic framework material is deposited on the Fe 3 O 4 On the surface of the particles, an organic shell of a certain thickness is formed, with a maximum thickness of about 25nm. The characterization results show that COF has been successfully composited with Fe 3 O 4 NPs surface.

[0093] In summary, Example 2 uses different characterization methods to verify the Fe 3 O 4 @TAPOB-COF magnetic material was successfully synthesized.

[0094] Example 3Fe 3 O 4 @TAPOB-COF magnetic material performance verification

[0095] In this example, Fe synthesized in Example 1 is selected. 3 O4 After pre-treating the environmental water with @TAPOB-COF, the PAEs plasticizers in the environmental water were determined by LC-MS / MS. The detection process is as follows Figure 1 shown.

[0096] Here’s how:

[0097] (1) The Fe synthesized in Example 1 3 O 4 @TAPOB-COF mixes with ambient water;

[0098] (2) Ultrasonic magnetic attraction to separate unabsorbed impurities;

[0099] (3) Ultrasonic desorption;

[0100] (4) filtering the magnetic nano-COF material treated in step (3) through a 0.22 μm nylon 66 organic filter membrane;

[0101] (5) LC-MS / MS determination of PAEs plasticizers in environmental water bodies.

[0102] The details are as follows:

[0103] 1. Instrumental analysis method:

[0104] Chromatographic column: Agilent EclipsePlus C18 column (50mm×2.1mm, 1.8μm). Mobile phase: phase A (0.2% formic acid in water) and phase B (methanol). The initial flow rate was 0.4mL / min at 35℃ column temperature by gradient elution program, and the injection volume was 5μL. Gradient elution program: 0~5min, 50%→50%B; 5~12min, 50%B→95%B; 12~18min, 95%→50%B; 18min, STOP.

[0105] The MS signals of the analytes and internal standards (IS) were detected by the multiple reaction monitoring (MRM) mode of the mass spectrometer, and the electrospray ionization (ESI) was performed in the positive ion mode. 100 μg / L of standard solution and 1.0 mg / L of IS solution were directly introduced to optimize the ion source and other MS / MS parameters. Pure nitrogen (>99%) was used as the nebulizer gas and drying gas, and high-purity nitrogen (>99.999%) was used as the collision gas. The gas flow rate was 13 L / min, and the sheath gas flow rate was 11 L / min. The ion source temperature was controlled at 300°C, and the sheath gas temperature was controlled at 250°C. The capillary voltage was 4000 V, and the nozzle voltage was 1500 V. The pressure of nitrogen in the nebulizer was 35 psig. DMP, DEP, BBP, DBP, DEHP, DNOP and DMP-d 4 , DEP-d 4 , BBP-d4 , DBP-d 4 , DEHP-d 4 DNOP-d 4 The optimized MRM conditions for (IS) are shown in Table 2.

[0106] Table 2 Mass spectrometry analysis conditions

[0107] Note: * is the quantitative ion, CE is the collision energy

[0108]

[0109] 2. Confirmation and validation of analytical methods

[0110] This embodiment carries out methodological research, including linearity, accuracy (recovery rate), precision, stability and detection limit (LODs). 10 μL water sample containing 100 μg / L internal standard is injected into LC-MS / MS for quantitative analysis. After the series of injection and detection of 6 kinds of PAEs standard solutions, the data is processed by the Quantitative Analysis software of the liquid quality control to obtain the standard curve equation and the corresponding linear correlation coefficient. The blank water sample is spiked at three different concentrations, namely high, medium and low concentrations, and the prepared standard working sample solution is obtained after adsorption and desorption treatment by magnetic covalent organic framework material. The relative standard deviation (RSD%) of three repeated tests is used to evaluate the precision of the method. The stability of the method is evaluated by the relative standard deviation of repeated injections (n>15) within and between days after sample pretreatment. The accuracy (recovery rate) of the method is evaluated by dividing the detected concentration of PAEs by its spiked concentration. The limits of detection (LODs) were calculated as three times the signal-to-noise ratio of the lowest standard concentration of PAEs, and the limits of quantification (LODs) were calculated as ten times the signal-to-noise ratio of the lowest standard concentration of PAEs.

[0111] Six mixed standard solutions of PAEs were prepared by stepwise dilution method (external standard solution concentration range was 1.0-1000 μg / L, internal standard solution concentration was 10 μg / L), and mass spectrometry was used for detection. Fig. 9The chromatograms of the six PAEs external standard mixed standards (including internal standards) with a concentration of 100 μg / L are shown in Table 3. The results in Table 3 show that there is a good linear relationship between the concentration (x, μg / L) and the peak area ratio (y) of the six mixed standard solutions in the range of 1 to 1000 μg / L (R>0.999). The limits of detection (LODs) are 0.00014 to 0.022 μg / L, and the limits of quantification (LOQs) are 0.00046 to 0.073 μg / L. Compared with the liquid chromatography-triple quadrupole mass spectrometry method in the Ministry of Environmental Protection standard ([2] Ministry of Ecology and Environment of the People's Republic of China. Determination of six phthalates in water quality by liquid chromatography-triple quadrupole mass spectrometry: HJ 1242-2022 [S]. Beijing: China Environmental Science Press, 2022.), this method has a sensitivity that is 40 to 8181 times higher than the national standard method.

[0112] Table 3 Linear range, minimum detection limit and quantification limit

[0113]

[0114] 3. Optimization of experimental conditions

[0115] The adsorption effect of PAEs plasticizer was optimized experimentally under different adsorption material dosage, adsorption time, adsorption temperature and initial concentration conditions. The Langmuir model was used to fit the experimental data and the theoretical maximum adsorption capacity of Fe3O4@TAPOB-COF composite material for PAEs plasticizer was calculated.

[0116] The adsorption rate formula is shown below.

[0117]

[0118] AR% represents the adsorption rate of each PAEs plasticizer.

[0119] C 0 It indicates the concentration of the PAEs plasticizer before adsorption.

[0120] C 1 It indicates the concentration of the PAEs plasticizer after adsorption.

[0121] 3.1 Optimization condition settings:

[0122] In order to optimize the adsorption of PAEs in water samples, the ultrasonic adsorption time, TAPOB:Fe 3 O 4 NPs@SiO 2 @DHA ratio, Fe 3 O 4The dosage of TAPOB-COF composite material, the volume of desorbent, different types of desorbents and desorption time were optimized. In the optimization of this experimental method, a certain amount of PAEs was added to pure water to prepare simulated water samples.

[0123] Fixed Fe 3 O 4 @TAPOB-COF material dosage was 20 mg, and the effect of ultrasonic adsorption time of 5 min, 10 min, 20 min, 30 min, 40 min and 60 min on the adsorption of PAEs in simulated water samples was investigated. The sampling volume was 100 μL each time and then 100 μL of pure water was added at the same time.

[0124] Fixed Fe 3 O 4 @TAPOB-COF material dosage was 20 mg, 2 mL methanol was used as desorption reagent, and desorption was performed for 20 min. The TAPOB:Fe 3 O 4 @SiO 2 The ratio of @DHA is 1:1, 1:2, 2:1 (m(mg):m(mg)), which are called material 1, material 2, and material 3 respectively. The effects of different materials on the adsorption of PAEs were investigated. The effects of different materials on the adsorption of PAEs were investigated. The results showed that TAPOB:Fe 3 O 4 @SiO 2 @DHA ratios of 1 / 2 to 2 can meet the requirements. Material 2, that is, when the ratio is 1:2, subsequent experiments are carried out on simulated water samples.

[0125] According to the above conditions, Fe 3 O 4 @The effects of the dosage of TAPOB-COF materials on the adsorption of PAEs in simulated water samples were 1 mg, 5 mg, 10 mg, 20 mg and 50 mg respectively (as shown in Table 4 below). The results showed that the treatment of simulated water samples could meet the requirements when the dosage of composite material 2 was 20 mg, so 20 mg of composite material 2 was taken for the next step of optimization.

[0126] 20 mg of composite material 2 was fixed and desorbed for 20 min at acetonitrile volumes of 1 mL, 2 mL, 3 mL and 4 mL respectively. The effect of different acetonitrile volumes on the adsorption of PAEs in simulated water samples was investigated. The results showed that the treatment of simulated water samples could meet the requirements when the acetonitrile volume was 4 mL.

[0127] 20 mg of composite material 2 was fixed, and four different desorbents, acetonitrile, ethanol, methanol, and isopropanol, were selected for desorption for 20 minutes to investigate the effect of PAEs adsorption in simulated water samples. Taking DMP in PAEs as an example (as shown in Table 5 below), the results show that different desorbents will produce different desorption concentrations for different plasticizers. Acetonitrile, ethanol, methanol, and isopropanol can all meet the desorption requirements, but will be subject to certain volume restrictions, which may be related to their solubility in different plasticizers. Those skilled in the art can choose different desorption agents and volumes according to their own desorption requirements.

[0128] Finally, the effects of desorption times of 5 min, 10 min, 20 min, 30 min, 40 min and 60 min on the adsorption of PAEs in simulated water samples were investigated. The results showed that the concentration of the desorption reagent showed a fluctuating change. Most of the six PAEs reached their peak values ​​in about 10 min, so the desorption time was more than 10 min.

[0129] Comprehensive, the subsequent use of composite material II (ie TAPOB: Fe 3 O 4 NPs@SiO 2 @DHA ratio is 1:2), Fe 3 O 4 @TAPOB-COF dosage was 20 mg, 2 mL methanol was used for desorption, ultrasonic adsorption time was 40 min, and ultrasonic desorption time was 10 min for subsequent experimental research.

[0130] Table 4 Adsorption rate of 1-50mg magnetic COF material after adsorbing 100μg / L PAEs

[0131]

[0132] Table 5 Effect of desorption reagent type and volume on desorption rate

[0133]

[0134] 4. Method comparison

[0135] Table 6 Comparison between this method and the literature method

[0136]

[0137] It can be seen from Table 6 that the sensitivity of this method is 2 to 164 times higher than that of the magnetic material adsorption-LC-MS reported by the research group ([1] Huang Qiong, Liu Meijia, Zhu Qunying, et al. Determination of the contents of six phthalates in environmental water by high performance liquid chromatography-tandem mass spectrometry based on magnetic nanocomposites [J / OL]. Physical and Chemical Testing-Chemical Volume, 1-8 [2024-10-30]. http: / / kns.cnki.net / kcms / detail / 31.1337.tb.20240611.1350.002.html.), while the sensitivity of DEP is not much different; compared with the literature ([2] Ministry of Ecology and Environment of the People's Republic of China. Determination of six phthalates in water quality by liquid chromatography-triple quadrupole mass spectrometry: HJ 1242-2022[S]. Beijing: China Environmental Science Press, 2022.) Compared with the liquid-liquid extraction-LC-MS in the literature ([3] Hong Xin. Establishment and application of simultaneous detection method for 9 phthalate plasticizers in environmental water [D]. Yantai: Yantai University, 2020.), the sensitivity of this method is increased by 32 to 8182 times; compared with the MOF magnetic material adsorption-GC-MS reported in the literature ([4] Wang Ting. Trace analysis and adsorption performance of organic pollutants by MIL-101(Cr) and its magnetic composite materials [D]. Shenyang: Shenyang Pharmaceutical University, 2016.), the sensitivity of DEP in this method is increased by 2 to 143 times, while the sensitivity of DMP is not much different. Therefore, the magnetic nanocomposite material in this method has obvious advantages in determining the 6 PAEs plasticizers in environmental water.

[0138] 5. Saturated adsorption test

[0139] To further investigate Fe 3 O 4 @TAPOB-COF magnetic covalent organic framework material adsorption mechanism of PAEs, this experimental study uses adsorption isotherm to evaluate the adsorption equilibrium, which describes the relationship between the equilibrium adsorption amount and equilibrium concentration of the adsorbent at a certain temperature. Weigh 20mg Fe 3 O 4 @TAPOB-COF was added to 10 mL of simulated water samples containing 6 kinds of PAEs at concentrations of 20, 50, 100, 200, 500 and 1000 μg / L. The adsorption was carried out under the above optimized conditions. The concentration of each PAEs in the supernatant was determined by LC-MS / MS. The experimental data were fitted with the Langmuir model to calculate Fe 3 O 4@TAPOB-COF magnetic covalent organic framework material has the theoretical maximum adsorption capacity of 6 PAEs and explains its adsorption mechanism (as shown in Formula 2).

[0140] Langmuir adsorption isotherm model:

[0141]

[0142] C e is the PAEs concentration when adsorption equilibrium is reached, μg / L;

[0143] q e is the adsorption amount when adsorption equilibrium is reached, μg / g;

[0144] q m Fe 3 O 4 @The maximum adsorption capacity of TAPOB-COF, μg / g;

[0145] K L is the Langmuir model constant;

[0146] The corresponding curves were fitted by the Langmuir model at room temperature (25°C), and the maximum adsorption amounts of DMP, DEP, BBP, DBP and DEHP were 312, 500, 714, 128, 1111 and 620 μg / g, respectively. It can cope with the determination of PAEs in more possible environments and has broad application prospects.

[0147] Stability and repeatability testing of composite materials

[0148] To further evaluate the Fe 3 O 4 @TAPOB-COF composite material stability. Under the optimized pretreatment conditions, a 50 μg / L mixed standard solution of 6 PAEs was prepared, using 20 mg Fe 3 O 4 @TAPOB-COF composite material was subjected to ultrasonic adsorption for 40 minutes, and then desorbed with 2 mL of methanol for 10 minutes. The adsorption-desorption-adsorption process was repeated 6 times. The RSD% of the PAEs concentration in the desorbed liquid was less than 5% and the recovery rate was not less than 75%, indicating that the material had undergone 6 adsorption-desorption processes and still had good adsorption capacity for 6 PAEs. A certain amount of the composite material was placed in a drying oven and heated to 300℃ for 2 hours, then cooled to room temperature, and then immersed in weak acid and weak base solutions for 6 hours respectively. After being taken out and washed with distilled water, it was used for repeated adsorption determination of 6 PAEs, and still had good reproducibility. Compared with the research group's literature [1], the number of repeated uses increased from 5 times to 6 times, and the high temperature stability was improved from 200℃ to 300℃.

[0149] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0150] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. Magnetic nano COF material, characterized in that: The magnetic nano COF material comprises an inner core and a COF outer layer, wherein the inner core contains Fe3O4@SiO2; the COF outer layer contains TAPOB, and preferably, the inner core further contains DHA, and the inner core and the COF outer layer are connected by DHA.

2. The magnetic nano-COF material according to claim 1, characterized in that: The Fe3O4@SiO2 and the DHA are connected by condensation of amino groups and aldehyde groups.

3. A pretreatment reagent, characterized in that The pretreatment reagent contains the magnetic nano-COF material as described in claim 1 or 2. Preferably, the pretreatment reagent also contains a desorption reagent, and the desorption reagent is selected from acetonitrile, ethanol, methanol or isopropanol.

4. A method for preparing the magnetic nano-COF material according to claim 1 or 2, characterized in that: The steps include: (1) Synthesis of Fe3O4@SiO2 magnetic microspheres; (2) amination of the Fe3O4@SiO2 magnetic microspheres to form NH2-Fe3O4@SiO2; (3) reacting DHA with the NH2-Fe3O4@SiO2 to generate Fe3O4@SiO2@DHA; (4) reacting the Fe3O4@SiO2@DHA with TAPOB to generate the magnetic nano-COF material, namely Fe3O4@TAPOB-COF.

5. The method according to claim 4, characterized in that The ratio of TAPOB to Fe3O4@SiO2@DHA is 1 / 2 to 2.

6. Use of the magnetic nano-COF material according to claim 1 or 2 and the pretreatment reagent according to claim 3 for determining PAEs plasticizers; preferably, the use is to determine PAEs plasticizers in environmental water.

7. The use as claimed in claim 6, characterized in that The PAEs plasticizer is selected from dioctyl phthalate, dimethyl phthalate, di(2-ethylhexyl) phthalate, butyl benzyl phthalate, diethyl phthalate or dibutyl phthalate.

8. A pretreatment method for determining PAEs plasticizers in environmental water, characterized in that: The following steps are included: (1) mixing the magnetic nano-COF material of claim 1 or 2 with environmental water; (2) Ultrasonic magnetic attraction to separate unabsorbed impurities; (3) Ultrasonic desorption.

9. The pretreatment method as claimed in claim 8, characterized in that The ultrasonic magnetic adsorption time is more than 20 minutes, the ultrasonic desorption time is more than 10 minutes, and the desorption reagent used in the ultrasonic analysis is selected from acetonitrile, ethanol, methanol or isopropanol.

10. A method for determining PAEs plasticizers in environmental water, characterized in that: The method comprises the pretreatment method and the detection method of claim 8 or 9, wherein the detection method is selected from gas chromatography, liquid chromatography, gas chromatography-mass spectrometry, liquid chromatography-mass spectrometry, micellar electrokinetic capillary chromatography or Fourier transform infrared spectroscopy, and preferably, the detection method is liquid chromatography-mass spectrometry.

Citation Information

Patent Citations

  • Magnetic covalent organic framework material as well as preparation method and application thereof

    CN112126071A

  • Triazinyl covalent organic framework material as well as preparation method and application thereof

    CN117209698A

  • Polyamide acid ion exchange membrane as well as preparation method and application thereof

    CN117443214A

  • Separation-ionization integrated mass spectrum ionization element and device for aflatoxin compound detection and application

    CN118841311A